Production Layout Optimization to Reduce Transportation Waste and Improve Process Cycle Efficiency in Passenger Seat Assembly - Amrin Amrin; Feby Gusti Dendra; Ahlandika Wirasatria (Universitas Islam Raden Rahmat, Malang, 2026)
Passenger seat assembly is a critical process in bus manufacturing because it directly affects production completion and delivery performance. This study aimed to optimize the production layout to reduce transportation waste and improve Process Cycle Efficiency (PCE) in the passenger seat assembly process of a bus manufacturing company. A quantitative case study was conducted using data collected through direct observation, time studies, interviews, and questionnaires. The analysis integrated Value Stream Mapping (VSM), Waste Assessment Model (WAM), Value Stream Analysis Tools (VALSAT), and Process Activity Mapping (PAM) to identify dominant waste and develop layout improvement strategies. The results showed that transportation waste was the dominant waste, accounting for 18.37% of the total waste score. The proposed layout reduced the number of activities from 36 to 32, decreased transportation time from 72.1 to 14.8 minutes, and eliminated all non-value-added activities. Consequently, lead time decreased from 543.03 to 456.67 minutes, while Process Cycle Efficiency increased from 51.64% to 61.88%. These findings demonstrate that lean-based production layout optimization effectively reduces transportation waste and improves operational efficiency in make-to-order bus manufacturing.